Macroeconomics - Gartner, Manfred (Pearson, 2013)
Macroeconomics continues to successfully combine theory and application, using many real-world case studies and examples, updated and changed for the fourth edition, to explain the basics of Macroeconomics and keep ahead of the ever changing macroeconomic environment we are experiencing today. This rigorous and comprehensive text offers a truly European and Global perspective ideal for intermediate and applied macroeconomics students.